Pengaruh Reputasi Institusi Terhadap Keputusan Mahasiswa Memilih Studi Manajemen di Universitas Negeri Makassar - Mukammil, Ahmad; Ramli, Anwar; Ruma, Zainal (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The purpose of this study was to determine the effect of institutional reputation on students' decisions to choose management studies at Makassar State University. Data collection was carried out by distributing questionnaires to respondents. The sample used in this study amounted to 88 respondents. The data analysis technique in this study used a simple linear regression test and hypothesis testing used a partial test and the coefficient of determination. The results showed that Institutional Reputation had a significant value of 0.001 less than 0.05 and with a regression coefficient of 0.724 in a positive direction, it means that Institutional Reputation has a positive and significant effect on Student Voting Decisions.